Gamification in HR management: Increasing Employee Motivation and Competence Through an Interactive Approach - Jahri, Muhammad; Norjannah, Norjannah; Mahyudiansyah, Mahyudiansyah (PT. Anagata Sembagi Education, 2025)
This study aims to examine how the application of gamification in human resource management (HR) can increase employee motivation and competence through an interactive approach. Gamification is the application of game elements in a non-game context, such as point systems, badges, leaderboards, and challenges, to make HR tasks more interesting and challenging. In this study, various case studies from companies that have successfully implemented gamification in their HR processes were analyzed to identify the benefits, challenges, and impact on employees. The results showed that gamification can significantly increase employee motivation by rewarding certain achievements and through healthy competition that promotes skill improvement. In addition, interactive approaches in gamification, such as team challenges and collaborative tasks, are able to increase employee engagement and active participation. Technology plays an important role in supporting the implementation of gamification, allowing these programs to be easily accessed and effectively evaluated. Evaluations and assessments show that a well-designed gamification program can create a dynamic and enjoyable work environment, which in turn increases productivity and job satisfaction. The study concludes that gamification is an effective tool to increase employee motivation and competence in HR management and has great potential to develop in the future.